Mechanism of Caffeine Enhancement of Mutations Induced by Sublethal Ultraviolet Dosages - Sideropoulos, Aris S. (1968)
Certain chemical compounds increase mutation frequency of Escherichia coli B/r significantly when used in conjunction with nonlethal ultraviolet (UV) dosages. Studies were done to elucidate the mechanism of this enhancing mutational effect. Dark survival curves showed that 500 μg of caffeine per ml in the postirradiation medium markedly decreased survival to 60 ergs/mm(2) of UV in strain B/r. Caffeine did not markedly decrease survival to UV in strain B/r WP-2 hcr(−). At least 90% of the mutations induced to streptomycin resistance by UV and 85% of those induced by UV with caffeine could be photoreversed. Experiments with thymine analogues suggested that thymine dimerization at the streptomycin locus was the primary premutational photoproduct induced by sublethal UV dosages. Caffeine did not interfere with the photoreversal of induced mutants, indicating that it probably does not bind to the photoreactivating enzyme or to a UV-induced lesion in the DNA. Addition of DNA or irradiated DNA with 500 μg of caffeine per ml resulted in no loss of the caffeine activity. The excision of UV-induced thymine-containing dimers from E. coli B/r T(−) was investigated in the presence and absence of caffeine. Our results indicated that caffeine prevents excision of thymine dimers, presumably by binding to the excising enzyme. This binding results in an impairment of repair, which produces the increase in mutant numbers.